The Role of Lithological Characteristics in Determining Landslide Susceptibility: Evidence from Tegalwaru District, West Java, Indonesia - Cahyati, Fajar; Heridadi; Adi Subiyanto; Rachmat Setiawibawa; Anwar Kurniadi (International journal of technology and education research, 2025)
This research examines the influence of lithological characteristics on landslide susceptibility in Tegalwaru District, Purwakarta Regency. The area is predominantly composed of claystone formations from the Jatiluhur Formation, which exhibits impermeable and porous properties. During high-intensity rainfall events, water infiltration becomes limited, resulting in rapid saturation of the surface layer. These conditions trigger soil softening and reduce slope stability in areas characterized by steep to very steep terrain gradients. Additionally, weathered volcanic fragments of andesite and diorite that comprise this region undergo intensive weathering processes, forming joint systems and boulders that are susceptible to movement. These lithological factors are further aggravated by high precipitation and anthropogenic activities, which collectively influence slope stability. This research emphasizes the critical importance of understanding lithological characteristics for effective landslide risk mitigation and disaster management planning.